The Legal Status Of Land Tenure Of Foreign Nationals Obtained Through Public Auction On The Object Of Mortgage Rights - Patriana Purwa; Geta Ilham Adi Prasetyo; Budi Salman Farizy; Mariam Pratama; Aslan Noor (Magister Kenotariatan Universitas Pasundan, 2023)
The concept of citizenship stipulates that non-citizens are prohibited from acquiring land ownership in Indonesia, meaning that